TGFβ1 evokes myoblast apoptotic response via a novel signaling pathway involving S1P4 transactivation upstream of Rho‐kinase‐2 activation. Issue 11 (2nd August 2013) - Cencetti, Francesca; Bernacchioni, Caterina; Tonelli, Francesca; Roberts, Edward; Donati, Chiara; Bruni, Paola
Abstract : In view of its multiple detrimental effects, transforming growth factor β1 (TGFβ1) is recognized as critical negative regulator of skeletal muscle repair. Apoptosis of skeletal muscle precursor cells driven by TGFβ1 contributes to the negative role exerted by the cytokine in tissue repair, although the underlying molecular mechanisms are still elusive. Herein we report the identification of a new signaling pathway, relying on Rho kinase‐2 stimulation, subsequent to SMAD‐dependent S1P4 up‐regulation and transactivation via sphingosine kinase (SK)‐2, that accounts for TGFβ1‐induced apoptosis in cultured myoblasts. S1P4 ‐specific gene silencing reduced by almost 50% activation of caspase‐3 and poly‐ADP ribosyl transferase cleavage elicited by TGFβ1. Moreover, the selective S1P4 antagonist CYM50358 also reduced the TGFβ1 proapoptotic effects. By employing pharmacological and molecular biological approaches, the involvement of SK2 and ROCK2 in the transmission of the TGFβ1 apoptotic action was also demonstrated. These results reinforce the notion that the SK/S1P axis plays a fundamental role in TGFβ1 mode of action in skeletal muscle cells and, by disclosing a novel mechanism by which TGFβ1 exerts its harmful action, pinpoint new molecular targets that in principle could be beneficial in the treatment of several skeletal muscle disorders or aging‐dependent muscle atrophy.—Cencetti, F., Bernacchioni, C., Tonelli, F., Roberts, E., Donati, C., Bruni, P. TGFβ1 evokes myoblast apoptotic response via a novel signaling pathway involving S1P4 transactivation upstream of Rho‐kinase‐2 activation. FASEB J . 27, 4532–4546 (2013). www.fasebj.org